Zimbabwean Communities in Britain Imperial and Post-Colonial Identities and Legacies - Zembe, Christopher Roy (Springer International Publishing, 2018)
This book examines why Zimbabwean immigrants in Britain should be viewed as a product of ethno-racial identities and prejudices developed and nurtured during the colonial and post-colonial phases of Zimbabwe's history. In the absence of shared historic socio-economic or cultural commonalities, the book will tackle the key question: 'Are Zimbabweans in Britain demarcated by race and ethnicity an imagined community?' Through an analysis of personal interviews, and secondary and primary sources, it identifies and engages historical experiences that had been instrumental in constructing diasporic identities and integration processes of Zimbabwean immigrants. With most literature tending to create perceptions that Zimbabwean immigrants are a monolithic community of Blacks, the book's comparative analysis of Blacks, Whites, Coloureds and Asians unveils a multi-racial community fragmented by historic racial and ethnic allegiances and prejudices. It is essential reading for scholars and researchers interested in migration, African Diaspora, and colonial and post-colonial studies.